Temperature effects on the seed germination of some perennial and annual species of Asteraceae family - Zarghani, Hadi; Mijani, Sajad; Nasrabadi, Samieh Eskandari; Ghias-Abadi, Mohhamad; Khorramdel, Surur; Azimi, Reyhaneh (Plant Breeding and Seed Science, 2014)
Temperature is the most critical factor determining success or failure of plant establishment. Seed germination response of five medicinal species include three seed-propagated perennial species, Cichorium intybus, cynara scolymus and Echinacea purpurea and vegetative-reproduction perennial species, Achillea millefolium and annual species, Matricaria aurea were assessed at constant temperatures. The seeds were exposed to constant temperatures of 5, 10, 15, 20, 25, 30, 35, 40 and 45°C under total darkness. Germination percentage of all the species were significantly affected by various temperatures (p ≤ 0.001). A. millefolium did not germinate at 5-10 and 35-45°C, but showed noticeable germination percentage (73.3-100%) at temperatures ranged from 15-30° C. The highest total germination percentage was observed within the range of 15-35 °C for other species. Also, we calculated cardinal temperatures (the minimum, optimum and maximum temperature) for seed germination of species. The highest value for minimum temperature was 10.07ºC in A. millefolium followed by C. scolymus and M. aurea (5ºC) while the lowest was for E. purpurea and C. intybus (2.68 and 2.90ºC respectively). The lowest value for optimum temperature was detected in A. millefolium (22.72ºC) and M. aurea (23.88°C) while the maximum values were observed in E. purpurea and C. intybus (30.40ºC and 29.90ºC respectively). Based on results of present study we concluded that species with both vegetative and seed-propagated reproduction forms like A. millefolium had smaller temperature range rather those with just one way of reproduction (seed production).